Volatility Spillovers Among the Three Places Across the Taiwan Strait: Evidence from a BEKK‐CARR Approach. (16th January 2023) - Wu, Chun Chou; Xu, Wen
Abstract: This study introduces a new BEKK‐CARR model to explore the volatility spillover effects among mainland China, Hong Kong, and Taiwan stock markets during the COVID‐19 pandemic. We also extend the approach of Diebold and Yilmaz (2009, 2012) to infer a brand‐new volatility spillover index to discuss the bi‐directional volatility transmission. Our results show that the trading information flow among these three markets has changed significantly as a result of the COVID‐19 pandemic. The strength of volatility spillover is increasing during this momentous period. The Hong Kong stock market plays a pivotal role in volatility transmission. The values for half‐lives by exogenous shocks keep relatively low during the pandemic period. A reasonable explanation is that the trading information transmissions among stock markets are quicker than in the non‐pandemic period.